Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.4 - Multiplying Polynomials - 4.4 Exercises - Page 306: 106



Work Step by Step

We are given that $f(x)=3x$ and $g(x)=6x-8$. We know that $(fg)(x)=f(x)\times g(x)$. Therefore, $(fg)(x)=(3x)\times(6x-8)=3x\times6x+3x\times-8=18x^{1+1}+(-24x)=18x^{2}-24x=18x^{2}-24x$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.